Strategi Inovasi Dakwah Abi Azkakia melalui Platform Digital Mobile Legends - Lu'lu'il Maknun; Suwendi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study aims to explore the transformation and strategies of da'wa (Islamic preaching) carried out by Abi Azkakia through the Mobile Legends platform. Employing a qualitative approach, the research delves into the way Abi Azkakia utilizes this digital game as a medium for religious outreach. Contrary to the argument proposed by Mubarok and Suklani, which suggests that Mobile Legends negatively impacts educational continuity, this study posits that the game, when integrated with social media, can serve as an effective channel for conveying religious messages, particularly when addressing youth who tend to be disengaged from conventional forms of da'wa. Based on data collected through interviews, observations, and document analysis, the research finds that Abi Azkakia's da'wa innovation evolved from educational settings to the strategic use of mobile gaming. The study concludes that there has been a significant transformation in both the innovation and strategies employed in his da'wa efforts.